Profitability and resource-use efficiency of tomato production in Lalitpur District, Nepal - Giri, Avishek; Shrestha, Aavash; Kafle, Nischal; Sai, Rijwan (Indonesian Journal of Agricultural Research, 2025)
Tomato (Solanum lycopersicum L.) is one of the most commercially important and widely cultivated vegetable crops in the mid-hills of Nepal. Protected cultivation methods like polyhouses and rain shelters offer promising opportunities for improving yield and income, particularly during the off-season. However, limited empirical evidence exists on the economic viability and resource use efficiency of such practices at the local level. The study was conducted in the Lalitpur area to evaluate the profitability and resource use efficiency of tomato production. Primary data were gathered from 68 tomato producers using a pre-tested semi-structured questionnaire. The benefit-cost ratio was 1.15, indicating that tomato cultivation in the study area is profitable, with farmers earning an additional 15 paisa for every rupee invested. The analysis revealed that plant protection, fixed cost, and micro-nutrient had a positive and significant effect on gross returns from tomato cultivation, while other expenses (machinery operation, maintenance & irrigation) had a negative and significant effect. The return to scale was 1.23, indicating increasing returns to scale. Additionally, resources such as seed, plant protection, and micro-nutrients were found to be underutilized, while fertilizers, labor, fixed variables, and other inputs such as irrigation and machinery costs were overutilized. Therefore, improving profitability in tomato cultivation can be achieved by reducing expenditure on overutilized resources and increasing investment in underutilized resources. The findings have important implications for farmers, extension workers, policymakers, and future researchers.